Implementación de un sistema de control interno y su influencia en el área de abastecimiento de la Municipalidad Distrital de San José - Pacasmayo, periodo 2017 - Guanilo Palomino, Leonid Edilberto (2019)
ABSTRACT This investigation has like intention determine the influence that has implementation of control sistem inter in the area of San Jose distrital municipality. A control sistem inter let to on entity develop the process of efficient way, already that yourlineament beginningcomponets can detect failure or mistakes thet deviate the obtaining of objectives of the entity. The problemn that proposed this investigation was how the implementation of control sistem intern affect in of supplying San Jose – Pcasmayo distrital municipality b period 2017?. In this case worked with a signm no probabilistic and and was conformed by workes of area of San Jose distrital municipality wich applyed the technique of poll. To come the conclusión that all polted are agreed that implement a control sistem intern in San Jose distrital Municipality already this influence of eficient way in the area ofsupplying. Finally to recommend implement a control sistem intern in the area of supplying.